Sharia Cryptocurrency Regulations and Fatwas: A Maqasid Shariah Analysis Regulasi dan Fatwa Kripto Syariah: Analisis Maqasid Syariah - Ramadhan, Ahmad Syauqi Azmi; Sukti, Surya (Journal of Law, Politic and Humanities, 2025)
Abstract: The growing use of cryptocurrency has triggered debates about its compatibility with Islamic law, especially in countries with a strong commitment to sharia economics. This study seeks to compare the legal regulations and religious fatwas on cryptocurrency in Indonesia and Malaysia, evaluated through the Maqasid Shariah framework. Using a normative-comparative legal approach, this research relies on statutory analysis, conceptual reviews, and cross-country comparisons. Key sources include DSN-MUI Fatwa No. 140/2021, Bappebti regulations, the Securities Commission Malaysia’s Guidelines on Digital Assets, and resolutions from the Shariah Advisory Council of Bank Negara Malaysia. Findings indicate that Malaysia shows stronger sharia governance through mandatory audits and public literacy initiatives, while Indonesia provides clearer legal certainty by codifying fatwas and regulations. These findings suggest that each country can learn from the other: Indonesia may strengthen governance, and Malaysia may enhance legal certainty. The contribution of this paper lies in its novelty of applying Maqasid Shariah to a comparative legal study of cryptocurrency, offering relevant implications for policymakers and sharia authorities.